From paper to pixels: using Google Forms for collaboration and assessment. Issue 4 (1st June 2015) - Djenno, Mireille; Insua, Glenda M.; Pho, Annie
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to discuss the use of Google Forms in the university library instruction classroom. Librarians at the Richard J. Daley Library at the University of Illinois at Chicago (UIC) began using Google Forms as a way of increasing active learning and as an instrument of formative assessment. The paper describes the information literacy context at the UIC and gives examples of best practices for using Google Forms in library instruction. Design/methodology/approach – The authors collaborated with other instruction librarians at their institution to develop Google Forms for use in library instruction sessions and used them primarily in sessions geared toward first-year students. Findings – Google Forms provides an easy and inexpensive way to incorporate both active learning and assessment in library instruction sessions. Students and faculty were receptive to their use in the library classroom. These early findings will be incorporated into the longer assessment study by the authors, currently underway. Originality/value – While Google Forms has heretofore been used in primary and secondary school settings, it is only now being more widely adopted for use by instruction librarians at the university level. This paper will be of value to those who wish to use Google Forms in library instruction in college and university settings, among others.